Formação continuada de Coordenadores Pedagógicos da Educação de Jovens e Adultos (EJA) da Rede Municipal de Educação de São Luís, Maranhão: proposições para a construção de práticas formativas inspiradas no pensamento de Paulo Freire - Cruz, Tatiana Rocha (2017)
The present study aimed at analysing the Continuous Professional Development for Pedagogical Coordinators in the Programme for Youth and Adult Education (EJA) in the Municipal Education System in São Luís do Maranhão, with a view to improve the formative practices inspired by Paulo Freire’s references. The theoretical grounding for the research was based on Freire’s work (1986,1988, 1995, 1996, 1997, 1998,2005) and on other authors whose thoughts are aligned with Freire’s, such as Apple (1997,1998); Nóvoa (1998); Saul, A.M. (2000, 2010,2016); André (2006); Feldmann (2008,2009); Santiago e Batista Neto (2011); Sacristán (1999); Mizukami et al. (2002); Gatti (2010,2011), amongst others. This study took into consideration, initially, for the purpose of analysis, documents from the federal realm, as well as propositions from the Municipal Education System in São Luís do Maranhão and, based on a qualitative approach to data analysis, aimed at capturing the perceptions from the subjects - pedagogical coordinators (CPs) and teachers (PROFs) - in reference to the continuous professional development offered by the Municipal Secretary of São Luís do Maranhão (SEMED) and the school units researched, between the years 2014 and 2015. The tools used for data collection in the field were: a questionnaire (given to pedagogical coordinators and teachers from 3 urban schools in São Luís, MA) and a semi-structured interview carried out with professionals from SEMED. The results emerged from data analysis and were systematized based on categories of analysis that surfaced from the theoretical reference, expressed through a conceptual tapestry based on the conception of permanent formation addressed in the work of Paulo Freire. Through the analysis of the data collected, it became clear that, although Freire’s references were stated in SEMED’s documents and proposals, there was a significant disparity between the prescribed practices and the reality, as perceived by EJA’s CPs and PROFs. Research data also point to a diverse and contradictory understanding regarding Freire’s concepts, which is the reason why proposals for the development of formative practices, inspired by the thought of Paulo Freire are put forward in this study